Using sosial cognitive theory to understand exercise maintenance in women breast cancer survivors adopting Guolin Qigong - Abdullah, Nadiah Diyana Tan; Khor, Poy Hua; Muhamad, Mazanah (Penerbit Universiti Malaysia Pahang, 2013)
The purpose of this study is to explore and understand the exercise maintenance in women with breast cancer survivors adopting Guolin Qigong using the Social Cognitive Theory related constructs. A qualitative approach using in-depth interviews were employed in this study. 22 participants of the Malaysia Guolin Qigong Association from five regions in Peninsular Malaysia were purposely selected to participate in this study. Data was collected through a series of audio-tapes during the interview sessions. They were asked on how do they maintain in their Guolin Qigong exercise. Three themes related to the Social Cognitive Theory constructs emerged from the data collected. (i) Personal Factors; (ii) Environmental Factors and (iii) Tailored Program. The belief in Guolin Qigong or in an exercise program is crucial in helping one to maintain with the exercise program and this findings is consistent with literature that those responded favourably to an exercise will have greater positive attitudes to exercise maintenance. To keep these women maintain the exercise it is important that these women have friends who understand them better to share their experiences related to their disease. It has been suggested that connecting to other survivors contributes to the survivors’ positive well-being and to deal with their everyday living. Lastly, the type of exercise should be tailored to the physical condition of these women to keep them sustain the exercise. This theory can be used by the health practitioners to develop more effective interventions for increasing exercise maintenance in sedentary cancer survivors by taking into special attention personal factors particularly one’s beliefs and inner motivation. Having to embark and engage into an exercise program of their preferred choice will help one to maintain an exercise program.